Potret History: Perkembangan MIN 2 Sambas Desa Sekuduk Sejangkung, Kalimantan Barat 1997-2023 - Olvi Andari; Beti Yanuri Posha; Manja Manja (Politeknik Kampar, 2024)
MIN 2 Sambas Sekuduk Village, Sejangkung District, Sambas Regency (West Kalimantan) is the first state-level Islamic educational institution which was founded in 1997. Previously known as the Aman Sentosa Sekuduk Private Ibtidaiyah Madrasah which was founded on December 27 1937. Of course, there are many aspects of change that have an impact on the development of madrasas. The aim of this research is to reveal the history of the development of MIN 2 Sambas, Sekuduk Village, Sejangkung District 1997-2023. The research method used is the historical research method, namely heuristic, verification, interpretation and historiography methods. From the research results, the history of the development of MIN 2 Sambas, Sekuduk Village, Sejangkung District from 1997-2023 is divided into periods based on the tenure of the madrasa head for the 1997-2001 period, the 2001-2009 period, the 2009-2013 period, and the 2014-2023 period. The development of each period of change and improvement certainly contributes to improving the quality of madrasas. This is felt by the school and the community of Sekuduk Village. Regarding the development of madrasas, infrastructure, teaching staff, students and school facilities are increasingly complete.